Agricultural trade liberalization and poverty in Brazil - Filho, Joachim Bento de Souza Ferreira (International Food Policy Research Institute, 2009)
This paper addresses the potential effects of a world agricultural trade liberalization scenario on poverty and regional income distribution in Brazil, using an interregional applied general equilibrium (AGE) and microsimulation model of Brazil, tailored for income distribution and poverty analysis. The model distinguishes 10 different labor types and 270 different household expenditure patterns. Income can originate from 41 different production activities (which produce 52 commodities), located in 27 states in the country. The AGE model is linked to a microsimulation model that includes 112,055 Brazilian households and 263,938 adults. The scenario is generated from a previous run of the MIRAGE model, which assesses the likely impacts of a Doha Development Agenda agreement, based on the draft on agriculture by Crawford Falconer and the draft on nonagricultural market access by Don Stephenson. The results of this global scenario are transmitted to the Brazilian model. Poverty and income distribution indexes are computed over the entire sample of households and persons, before and after the introduction of policy shocks. Model results show that the simulated trade policy shocks have positive effects on poverty and income distribution in Brazil. The simulated effects on poverty and income distribution are positive in aggregate, with benefits concentrated in the poorest households. The results, however, differ across the Brazilian territory, worsening in some important states, where the poverty and inequality indicators increase. The gains in agriculture are found to benefit all the agents involved, from workers to small producers to large farmers, rejecting the idea that just large farmers would gain.